AN EXPLORATORY CLINICAL TRIAL TO EVALUATE THE ROLE OF RAGA BAGESHREE ON BASURI AS MANASOANUGUN SHABDA CHIKITSA IN ANIDRA - Dr. Ankita Chavan; Dr. Arti Firke (Intemed: International Journal of Research in Integrated Medical Sciences (IJ-RIMS), 2026)
Ayurveda extends beyond a mere medical system; it represents a holistic way of life aimed at physical, mental, and spiritual well-being. Modern lifestyles, characterized by intense competition and chronic stress, have severely impacted basic biological needs like diet and sleep. Consequently, over half of the adult population experiences sleep disturbances1 , with insomnia being the most prevalent. In Ayurveda, this condition correlates with "Anidra". According to Ayurvedic principles, Diet (Aahar), Sleep (Nidra), and Celibacy (Brahmacharya) are the three foundational pillars (Upastambha) of health2 . Sleep occurs naturally when the mind (Mana) and sensory organs (Indriya) detach from their objects due to fatigue3. Conversely, insomnia arises from the aggravation of Vata and Pitta doshas, mental distress, trauma, or tissue depletion (Dhatu kshaya). To counter this, ancient texts advocate for "Manasoanugun Shabda Chikitsa" —the therapeutic use of pleasant, customized sounds or music4. Indian philosophy posits that the universe is vibrating with sound (Nada). Outer sounds (Ahata nada) received by the ears can profoundly influence physiological and psychological states. Certain musical frameworks, known as Ragas, generate specific therapeutic vibrations when played at their designated times (prahar). Raga Bageshree, an evening melody (2nd prahar of the night) 5, is characterized by the dominant notes "Ma" (Vadi) and "Sa" (Samvadi). Given its inherent calming properties, this study specifically utilized a flute rendition of Raga Bageshree to evaluate its efficacy in inducing sleep.